Post and neo-colonial proximities | exiting Varosha. A Visual Essay, published at Passeio, Art & Urban Culture Platform, A Platform for the study of art and urban culture, - Pericleous, Vicky (My University, 2023)
POST AND NEO-COLONIAL PROXIMITIES | EXITING VAROSHA This visual essay draws the trajectory of an uneasy spatiotemporal navigation into post and neo-colonial contexts and cultural disputes. It comes us a response to my, first ever, entry and peripatetic wondering(s) into the formerly enclosed area of Varosha, in the city of Famagusta (Ammochostos), Cyprus. It further expands on relevant disputes and ideas that relate my art practice’s propositions, research and works. Access the essay here. Bio Vicky Pericleous is a visual artist and assistant professor at Cyprus University of Technology, Department of Fine Arts. She has studied at Manchester Metropolitan University, Wimbledon School of Art, London, and the Academy of Fine Arts in Venice. Pericleous’ work investigates her interest in examining and producing images where environments, gestures and encounters oscillate between the familiar and the alien, the ruin and the model, and notions of the near and far, in respect to postcolonial situations and geographical and cultural imaginaries. The idea of the fragment as well as spatiotemporal proximities and speculations are negotiated throughout her artistic oeuvre. Her work has shown in exhibitions at various international venues including Espace Commines, Paris, Hasselblad Foundation in Gothenburg, Zahoor Ul Akhlaq Gallery of the National College of Arts, Lahore, Multiplied Art Fair, Christie’s, London as well as in various private galleries abroad [Amsterdam, Athens, Belgrade, Gothenburg, Istanbul, Lahore, London, Manchester, Paris, Rotterdam, and Vienna] in international exhibitions, biennales, curatorial research projects and programmes [ including Resilience /Compassion, 2022, Municipal Art Gallery, Athens, Vicky Pericleous/ ‘The Idle Fountain’, Solo Show, 2020-21, Art Seen Gallery Nicosia, ‘Drone Vision: Warfare, Surveillance, Protest’, across three countries/art Foundations, 2016-18, ‘The Presence of Absence, or the Catastrophe Theory’, NiMAC, Nicosia, 2018, ECLN Taking Part, Bernie Grant Arts Centre, London Monodrome, the 3rd Athens Biennale, and at Sanat Limani, as part of the European Capital of Culture Istanbul 2010]. Over the years, she has collaborated with and has been represented by Omikron Gallery, Nicosia (2010–2013) and Art Seen Gallery, Nicosia (2015–now). She has initiated and participated in the international visual-research project “Uncovered: Nicosia International Airport,” 2010-13. She has been an active member of the Noise of Coincidence Art Group, an international art group / platform that has organised several exhibitions, actions, happenings and talks in Cyprus and abroad. Her work has been published and presented in many acclaimed books, art catalogues and press, including book publications by the Valand Academy of the Gothenburg University in collaboration with the Hasselblad Centre in Gothenburg, Sweden, 2022 and University of Columbia Press, Sept. 2019. Her work has been featured and presented in international Art & Theory Magazines. Amongst them the research platform Perambuation, Daily Lazy International, Art Daily Newspaper International and Art Forum, Critic’s Picks Column. She has presented her work in many conferences, seminars, lectures and talks and she has contributed in the development of many Art Research Funded Programmes. Currently she is co-coordinating the Artistic and Creative Expression, (package 3) of the Creative Europe Programme: EMPACT (Empathy and Sustainability: The Art of Thinking like a Mountain), coordinated by the Cyprus University of Technology (CUT).
Keywords: Arts